Music composition realisation: the effectiveness of using musical instrument digital interface(MIDI) among music composition students / Nor Farahein Yacob - Yacob, Nor Farahein (Faculty of Music, 2016)
The revolution of technology helps the composition process in way that so many works could be done with all the software that we have today. The existence of musical instrument digital interface (MIDI) works as a medium for most of music producers in making music. This study is aiming to investigate the effectiveness of using musical instrument digital interface (MIDI) among music composition students. It is also to find out how the music compositions students perceive the importance of using MIDI for music notation and piano roll sequencing based on their preferred digital audio workstation software. Other than that, this study is to investigate the knowledge of music composition students using MIDI in realizing their works.